2019
DOI: 10.1038/s41587-019-0205-0
|View full text |Cite
|
Sign up to set email alerts
|

A divalent siRNA chemical scaffold for potent and sustained modulation of gene expression throughout the central nervous system

Abstract: Users may view, print, copy, and download text and data-mine the content in such documents, for the purposes of academic research, subject always to the full Conditions of use:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
245
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 155 publications
(262 citation statements)
references
References 50 publications
13
245
0
4
Order By: Relevance
“…Eine Repression der Genexpression im gesamten Gehirn durch kleine interferierende RNAs (siRNA) ist bisher noch nicht erreicht worden. Präklinische Studien zeigen, dass durch die Injektion divalenter siRNA (di-siRNA), aus zwei vollständig chemisch modifizierten und verbundenen siRNAs in das Ventrikelsystem, eine ausgeprägte, 50-bis 90 %ige Reduktion der HTT-Expression im ZNS erreicht werden kann, auch ohne Verwendung viraler Vektoren [23]. Bei Verabreichung an Makaken zeigte der Ansatz eine gute und gleichmäßige Verteilung über die beiden Hemisphären und führte zu einer deutlichen nichtallelselektiven Reduktion des HTT.…”
Section: Divalente Sirna Als Eine Innovative Methodeunclassified
“…Eine Repression der Genexpression im gesamten Gehirn durch kleine interferierende RNAs (siRNA) ist bisher noch nicht erreicht worden. Präklinische Studien zeigen, dass durch die Injektion divalenter siRNA (di-siRNA), aus zwei vollständig chemisch modifizierten und verbundenen siRNAs in das Ventrikelsystem, eine ausgeprägte, 50-bis 90 %ige Reduktion der HTT-Expression im ZNS erreicht werden kann, auch ohne Verwendung viraler Vektoren [23]. Bei Verabreichung an Makaken zeigte der Ansatz eine gute und gleichmäßige Verteilung über die beiden Hemisphären und führte zu einer deutlichen nichtallelselektiven Reduktion des HTT.…”
Section: Divalente Sirna Als Eine Innovative Methodeunclassified
“…In Europe, a prevalence of 3/100,000 is assumed, the highest prevalence occurs in Sicily with 9.8/100,000 affected islanders [6]. However, current studies show that the genotype frequency with intermediate (36)(37)(38)(39) and pathological (>39) expansion in the huntigtin gene (HTT) may be as high as 139/100,000 [7]. Genetically, HD belongs to the group of trinucleotide repeat expansion disorders.…”
Section: Genetics and Pathophyiology Of Huntington's Diseasementioning
confidence: 99%
“…While individuals with a CAG repeat length of less than 35 located on exon 1 of HTT remain asymptomatic, alleles with 40 or more repeats show full penetrance. Intermediate alleles (36)(37)(38)(39) bear an increased risk to develop HD. There is an inverse correlation between the age of onset, and the length of the CAG repeat expansion, whereby alleles with more than 70 repetitions always cause a manifestation in adolescence.…”
Section: Genetics and Pathophyiology Of Huntington's Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…For example, Dieguez-Hurtado et al [14] found that inactivating a transcription factor, RBPJ, post-natally alters pericyte function, causing vascular instability and lesions with some similarities to cerebral cavernous malformations, and greater injury after ischemic stroke. Another advance for manipulating the NVU and brain (experimentally and therapeutically) is the finding by Alterman et al [15] that a single CSF injection of divalent small interfering RNAs is effective in reducing huntingtin expression (mRNA and protein) throughout the mouse brain, with effects lasting for at least 6 months. They had similar results in cynomolgus macaques.…”
Section: Toolsmentioning
confidence: 99%